Kesenian yoga dalam kalangan etnik India - Rajaletchumy, V. (Universiti Malaysia Sarawak, UNIMAS, 2007)
The research aims to study the Indian community's perception of and exposure to Yoga as art form. Yoga will be discussed as an exercise, a method in becoming a yogi and form of mediation. Data and sources will be collected through distributing questionnaires and conducting in depth interviews with experts in the Yoga industry.